2010
DOI: 10.1007/s11033-010-0132-0
|View full text |Cite
|
Sign up to set email alerts
|

Does the geographical gradient of ApoE4 allele exist in China? A systemic comparison among multiple Chinese populations

Abstract: The allelic frequencies of apolipoprotein E (apoE) vary substantially around the world. There is a conspicuous south-to-north gradient of e4 frequencies in Europe, with the proportion of e4 carriers from only 10-15% in the south to 40-50% in the north. The mechanism may be related to the possibility that e4 carriers are less likely to develop vitamin D deficiency. In addition, Asian populations traditionally have lower e4 frequency than Europeans, which may be attributed in part to the scarce or irregular food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 33 publications
2
21
3
1
Order By: Relevance
“…However, there is great ethnic variation in APOE frequencies. The frequency of the APOE-ε4 allele in our population is 9.3%, which is in the range of that in Asian (including Chinese) populations (6.3-9.3%) [42,43,44], but lower than that in Caucasian and African American populations (11-27%) [45]. Multivariate analyses did not explore the presence of APOE-ε4 as an independent risk factor of dementia.…”
Section: Discussioncontrasting
confidence: 59%
“…However, there is great ethnic variation in APOE frequencies. The frequency of the APOE-ε4 allele in our population is 9.3%, which is in the range of that in Asian (including Chinese) populations (6.3-9.3%) [42,43,44], but lower than that in Caucasian and African American populations (11-27%) [45]. Multivariate analyses did not explore the presence of APOE-ε4 as an independent risk factor of dementia.…”
Section: Discussioncontrasting
confidence: 59%
“…All genotyping results (100%) were in accordance with the results of direct DNA sequencing. In the subjects (n=305), the overall allele distribution was similar to a previous study (34), with no significant difference in allele distribution (Chi-squared test, P=0.598). These results indicate the reliability of using the PCR-GoldMag LFA method for ApoE genotyping.…”
Section: Resultssupporting
confidence: 80%
“…17 Genetic polymorphism is another influential factor for these differences. Hu et al 18 found that positive correlation existed between the e4 allele frequency distribution and a northern latitude (r=0.586; P=0.008) in China. Many studies have shown that ICAS is associated with lipid disorder, 19 hypercholesterolemia, 20 tobacco use, 21,22 and diabetes mellitus.…”
Section: Discussion Geographic Difference In Icasmentioning
confidence: 99%